Аналіз сучасних розробок у галузі перетворення звукових хвиль в електричну енергію - Піцур, Ю. М.; Кулик, С. А. (ХНУРЕ, 2019)
Modern developments in the field of the creation of technologies and tools used in the field of alternative energy are very relevant. The trans-formation of sound waves into electrical energy is a complex scientific and technical task. In this study, an analysis of various projects on the transfor-mation of acoustic energy into electrical. It is determined that many fac-tors interfere with the wide use of these technologies, such as: restriction of ap-plication areas of converters; expensive in the manufacturing converter; low ef-ficiency.
Keywords: electrical energy; sound waves; creation of technologies